The Impact of Perceived Risk and Trust on Electric Vehicle Adoption in Sustainable Tourism Regions - Komang Bagus Lanang Prabawa; Putu Purnama Dewi; Ngakan Nyoman Kutha Krisnawijaya; A.A. Ngr. Eddy Supriyadinata Gorda (AIBPM Publisher, 2025)
The influence of perceived risk and marketing communication on electric motorcycle purchase choices in Bali is examined in this study, with technological trust serving as the mediating factor. Despite Bali's global acclaim as an eco-tourism hub dedicated to sustainable progress, electric vehicle uptake among residents lags behind official benchmarks. A quantitative survey methodology is employed, drawing data from local inhabitants and subjecting it to Partial Least Squares–Structural Equation Modeling (PLS-SEM) grounded in the Unified Theory of Acceptance and Use of Technology (UTAUT 3). Significant direct and indirect effects on purchase determinations channeled through trust in technology are revealed for both perceived risk and marketing communication. A pivotal mediation function is fulfilled by technological trust, whereby the adverse sway of perceived risk is attenuated and the favorable impact of marketing outreach amplified. Transparent, educational, and confidence-enhancing promotional tactics, coupled with enabling infrastructure and regulatory measures, are underscored by the outcomes as vital for hastening electric vehicle integration in tourism-centric sustainable locales.